Integration proposal for thermal imaging modality into health information systems - Vardasca, R.; Tereso, M.; Pratas, A.; Alturas, B.; Martinho, D.; Bento, F. (Advanced research in technologies, information, iInnovation and sustainability: Third International Conference, ARTIIS 2023, Proceedings, 2024)
Thermal imaging allows to map and record surface temperature in a form of images, which in medicine can document pathological states and be an important complimentary diagnostic and treatment monitoring method. It is available for six decades, but some factors contributed to its low adoption, being the main the lack of integration with the existing health information systems at the healthcare institutions. It is aim of this research to address the lack of integration with existing technological infrastructure, through documenting and proposing a procedure to integrate thermal imaging as an imaging modality in health information systems. Requirements will be outlined, supported by UML modulation for simple use cases and class diagram along with the steps to adopt the DICOM standard. Following the proposed methodology, it will be possible to integrate thermal images with the existing health information systems, contributing to better performance of the exam, increase interoperability, ensure data security and availability, and improved patient care and satisfaction.